Nanoscale redox mapping at the MoS2-liquid interface - He-Yun Du (Nature Portfolio, 2021)
Here, high-resolution atomic force microscopy and scanning electrochemical microscopy are used to investigate the electron transfer behaviour of layered MoS2 flakes in organic solutions, offering insights on the electronic band alignment at the solid-liquid interface.